BREUVAGE SYMBIOTIQUE à PARTIR DE DÉCHET ALIMENTAIRE - BENNOURINE, Soumia (My University, 2023)
This study aims to utilize food waste, specifically tea, by investigating its potential as a source of probiotic lactic acid bacteria for fermented beverages. The focus is on the nutritional composition and environmental impact of raw and brewed tea. Analyses revealed that green teacontains 165,893 mgEAG/g of polyphenols, and 174.11 mg EQ/g of flavonoids. Tannins are present at a content of 2,177.263 mg EC/g, sugar at 0.203%, proteins at 0.11 g, and fat contentat 5.32 g. The DPPH has an IC50 value of 1.232 μg/mL, the FRAP is 100.167 μg/mL, and theTBARS is about 1.836 mg E MDA/kg. Thus, green tea has a higher content of phenolic compounds, giving it superior antioxidant activity compared to black tea. Among the infusions, the green tea infusion at 20°C shows high antioxidant activity compared to other infusions, withan IC50 value of 0.277 μg/mL for the DPPH, an IC50 of 162.287 μg/mL for the FRAP, and 0.29 mg E MDA/kg for the TBARS. We also studied the content of polyphenols, flavonoids, condensed tannins, and proteins, which are respectively 541.54 mg EAG/g, 290.707 mg EQ/g,400 mg EC/g, and 0.073%.
Keywords: valorization; tea waste; lactic bacteria; antioxidant activity; fermented beverage